Open access in the humanities, arts and social sciences: Complex perceptions of researchers and implications for research support - Quigley, Niamh (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2021)
Adoption of open access in the humanities, arts and social sciences (HASS) is a work in progress, with lower engagement in HASS than most of the natural sciences. HASS research impacts how we live, how we learn and how we see ourselves, and research institutions should encourage and enable their HASS research communities to increase the prevalence of open access research outputs. Six experienced HASS researchers at a single academic institution in Perth, Australia, were interviewed to explore their perceptions and experiences of open access, and any barriers that they had encountered. Thematic analysis was used to code the transcribed interviews, and generate themes. This study found a wide variance in the adoption of open access practices among HASS researchers. Some participants are publishing via APC-based gold open access (in DOAJ listed journals), while other participants encounter multiple barriers to sharing more of their work as open access. Confusion about aspects of open access is evident. Even among participants who support open access, some have had poor experiences of open access publishing. This research also found that some participants hold extremely complex opinions on open access, which directly influence participants’ behaviour depending on which perspective they are considering. These perspectives are: research supervisor, editorial role at journal, funding assessor and global citizen. Within HASS a diversity of behaviours exists around open access, and research institutions need to tailor their research support services around open access and scholarly publishing for different communities of researchers.